NCD Care Continuum and Opportunities for Action within Health Reform in Ukraine - Zhao, Feng; Fraser, Nicole; Khan, Olga; Doroshenko, Olena; Poole, Laura (World Bank, Washington, DC, 2021)
Ukraine is amid a comprehensive health sector reform to transform the current unaffordable and inefficient system into a modern, more efficient, and affordable one. The country’s health system is not addressing non-communicable diseases (NCD) and chronic conditions effectively, and NCD-related health outcomes compare relatively poorly to countries with a similar level of health financing. The paper analyzed the continuum of care for four conditions (hypertension, diabetes, breast, and cervical cancer) using the cascade framework as an analytical tool and programmatic data from two regions of Ukraine (Lviv and Poltava). It draws on global evidence of good and cost-efficient practices and includes the findings from guided discussions with Ukrainian health care planners, administrators, and providers. The analysis found significant gaps in detection, treatment monitoring, and treatment adherence in hypertension care (the largest breakpoints were blood pressure monitoring and achieving treatment targets) and similarly in diabetes care (underdiagnosis, inappropriate or incomplete treatment monitoring, sub-optimal treatment success). In breast cancer care, there was inadequate screening coverage among eligible women, post-screening losses, and a lack of documentation regarding treatment outcomes. In cervical cancer care, the screening intervals for covered women were short, creating inefficiencies, while many women were not screened despite program eligibility, and there was also a lack of long-term monitoring of women who had undergone treatment. The authors discuss the methodological approach of analyzing routine medical records and cancer registry data and triangulating data across multiple data sources. Important lessons and policy implications include the need to revise sequence of services, focus on follow up and retention in care, develop systems for managing risk factors, and strengthen the monitoring and data recording of NCD cases. Improved NCD care would save lives, reduce disability, save resources in health care, and reduce the impact of NCDs on individuals and society.